Logic programming as a service in multi-agent systems for the Internet of Things. (25th June 2019) - Calegari, Roberta; Denti, Enrico; Mariani, Stefano; Omicini, Andrea
The widespread diffusion of low-cost computing devices, along with improvements of cloud computing platforms, is paving the way towards a whole new set of opportunities for Internet of Things (IoT) applications and services. Varying degrees of intelligence are required for supporting adaptation and self-management: yet, they should be provided in a light-weight, easy to use and customisable highly-interoperable way. In this paper we explore Logic Programming as a Service (LPaaS) as a novel and promising re-interpretation of distributed logic programming in the IoT era. After introducing the reference context and motivating scenarios of LPaaS as an effective enabling technology for intelligent IoT, we define the LPaaS general architecture, and discuss two different prototype implementations - as a web service and as an agent in a multi-agent system (MAS), both built on top of the tuProlog system, which provides the required interoperability and customisation. We finally showcase the LPaaS potential through two case studies, designed as simple examples of the motivating scenarios.